The Development of Instruments to Detect Indicators of Behavioral Changes in Therapeutic Communities: A Clinical Case Study - Cristofanelli, Stefania; Ando', Agata; Ferro, Laura (Frontiers in Public Health, 2019)
Clinicians involving in the treatment of adolescent patients should use a valid and efficient psychological assessment. The evaluation of the efficiency in clinical interventions may provide helpful information in terms of cost-effectiveness and may contribute to increase the quality and efficacy of the public services. Despite the importance of clinical and therapeutic interventions, we may observe several aspects limiting the chance in using them. For example, the neuropsychiatry context due to heterogeneous users (such as children and adolescents) makes the replicability of clinical trials difficult in terms of results. Thus, efficient clinical programs and interventions—potentially able to identify specific and long-term effects—need to be defined. In clinical contexts (i.e., therapeutic communities). It should be a priority both to manage aspects of emergency/urgency we may observe in adolescents, and to focus on those aspects placed on a timing dimension. The current study reports a description of innovative measures developed specifically for assessing adolescent patients and for tracking psychological features and behavioral changes. Furthermore, a clinical case is examined by using a multimethod assessment including such innovative measures. Clinical implications are discussed. The development and sharing of “assessment cultures” among professionals should represent a priority in improving the effectiveness of therapeutic communities.